2008
DOI: 10.1007/s10142-008-0102-y
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases controlling PCNA and p53 expression in human ovarian cells

Abstract: The aim of this study was to identify protein kinases (PKs) involved in the expression of proliferating cell nuclear antigen (PCNA) and p53, markers of proliferation and apoptosis in human ovarian cells. Cultured ovarian granulosa cells were subjected to transfection with 264 small-interfering RNA (siRNA) constructs from a siRNA library, which selectively blocked the expression of 88 known PKs. The efficiency of transfection and siRNA knockdown were validated by fluorescent microscopy, real-time reverse transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
1
9
0
1
Order By: Relevance
“…Genome-wide selected blockade of PKs by siRNAs showed, that 34% of PKs up-regulates, and less than 6% of PKs downregulate human ovarian granulosa cell apoptosis (Sirotkin et al, 2009). The involvement of PKA, PKG, MAPKs, PI3K, CDKs, TKs, and AK in control ovarian follicular cell apoptosis was shown by studies of effect of regulators of these PKs (Sirotkin et Fig.…”
Section: Protein Kinases Control Ovarian Cell Apoptosismentioning
confidence: 96%
See 2 more Smart Citations
“…Genome-wide selected blockade of PKs by siRNAs showed, that 34% of PKs up-regulates, and less than 6% of PKs downregulate human ovarian granulosa cell apoptosis (Sirotkin et al, 2009). The involvement of PKA, PKG, MAPKs, PI3K, CDKs, TKs, and AK in control ovarian follicular cell apoptosis was shown by studies of effect of regulators of these PKs (Sirotkin et Fig.…”
Section: Protein Kinases Control Ovarian Cell Apoptosismentioning
confidence: 96%
“…Furthermore, observations of effects of activators and blockers of PKs indicate presence and importance of a number of other PKs in control of ovarian functions and in mediating effect of hormones on these functions (see below). For example, blockade of 88 PKs by siRNA constructs altered ovarian cell functions (Sirotkin et al, 2009(Sirotkin et al, , 2010. Presence of PKA and CDK/p34 in ovarian follicles is illustrated in Figure 1.…”
Section: Presence Of Protein Kinases In the Ovarymentioning
confidence: 98%
See 1 more Smart Citation
“…3). Furthermore, a number of siRNAs silencing different protein kinases was able either to up-and down-regulate proliferation of ovarian granulosa cells (Sirotkin et al, 2009b). The ability of small RNAs to suppress ovarian cell cycle indicated that RNA interference could be useful tool to suppress over proliferating ovarian cancer cells.…”
Section: Rna Interference and Ovarian Cell Proliferationmentioning
confidence: 98%
“…Effect of some miRNAs on apoptotic markers are presented at Figure 4. A number of siRNAs targeting protein kinases was able either to promote or suppress the expression of apoptosis marker of ovarian granulosa cells (Sirotkin et al, 2009b). Numerous attempts have been made to use the ability of small RNAs to affect apoptosis for reducing viability of ovarian cancer cells and inducing their death.…”
Section: Rna Interference and Ovarian Cell Apoptosismentioning
confidence: 99%